Hydrogen/deuterium exchange in alkyl-hydride derivatives of ansa-tungstenocene compounds - Green, M; Conway, S; Doerrer, L (Elsevier, 2005)
The higher n-alkyl hydrides [W{(η-C5H4)CMe2(η-C5H4)}(R)H](R = {(CH2)nCH3}, n = 1–4) and the isotopically labelled analogues [W(η-C5D4)C(CD3)2(η-C5D4)}(R)D], (R = {(CH2)nCH3} (n = 1–4) and [W{(η-C5H4)CMe2(η-C5H4)}{CD2CD3}H] have been prepared and the hydrogen/deuterium exchange processes under thermal conditions in these compounds have been investigated by NMR spectroscopy. In every case of all the possible alkyl hydrogens of the alkyl groups R only H/D exchange with the α-CH2 methylene hydrogens was observed.